Polibio, Fabio Píctor y el origen del etnónimo “celtíberos” - Pelegrín Campo, Julián (Gerión. Revista de Historia Antigua, 2005)
A close examination of Polybius’ Histories points to the Greek Annales of Fabius Pictor as the origin of the name “Celtiberians”, a composed word created by the first Roman historian on the base of the similarities between the Celts invading Italy and the “Celts of Iberia” –this is the meaning of Keltivbhreı–, which successively fighted as mercenaries beside the Romans, the Carthaginians and diverse Iberian peoples during the Hannibalic War and the first decades of the Roman conquest of Hispania.